Quality of services as a vector for expansion and development of service activities - I. Yu. Sofiyannikova (Вестник университета)
The article studies problematic aspects of expansion and development of service activities in Russia. The main purpose of the study is to analyze problematic aspects of the service sphere development and existing and most popular methods of assessing the quality of services. The relevance of the study is due to the need to expand service in the country, considering orientation on the interests of the end consumer and with simultaneous improvement of service quality. The main objectives of the study are: to identify problematic aspects of development of service activities in Russia, to identify and analyze the shortcomings of the methods used by service enterprises to assess the quality of services, and to propose options for their minimization and elimination. The article used both theoretical methods (analysis of current regulatory legal acts, as well as scientific works of researchers in this field) and empirical research methods (practical substantiation of the need to improve the quality of services provided to customers). On the basis of the analysis of the most popular and frequently used methods of service quality assessment the advantages and disadvantages of their application have been revealed. The study results are the problems identification that have a negative impact on service activities development and proposal of possible options for their solution.